Insumos importados e evoluç\~ao do setor manufatureiro no Brasil - Nelson Marconi; Marcos Rocha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This paper analyzes the evolution of the share of imported intermediate goods in the production process and its influence on the share of manufacturing in value added for the Brazilian economy, covering the period span 1995-2008. In a first step, we estimate input-output matrices, at constant prices, that are used to calculate: i) the evolution of sectorial production costs; ii) an index of imported intermediate goods share in the productive process; and iii) an index of exporters' profitability. We assessed the evolution of these indices. In a second step, we use a panel SYS-GMM to perform econometric tests based on data disaggregated by sectors of manufacturing. The panel regression results show that the index of imported intermediate goods and the share of manufacturing in value added are negatively correlated, in a statistically significant way. This result can be explained by the hypothesis that entrepreneurs adopt a strategy to reduce costs so as to preserve profitability, by increasing the share of imported intermediate goods in intermediate consumption when they become cheaper. For the exporters, this is a strategy to remain competitive in the manufacturing sector when the exchange rate appreciates. As a result of this process, and due to the results obtained in the tests, it is possible to state that a process similar to the maquilla may be occurring in the country. In the long run, growth and persistence of this fact may contribute to significant reductions in the share of manufacturing in value added of the Brazilian economy.
Keywords: O11; O14; O24; F43; 330; deindustrialization; exchange rate; economic development; Vorleistungen; Import; Industrie; Input-Output-Analyse; Brasilien